De novo Transcriptome Profiling of Flowers, Flower Pedicels and Pods of Lupinus luteus (Yellow Lupine) Reveals Complex Expression Changes during Organ Abscission - Glazinska, Paulina; Wojciechowski, Waldemar; Kulasek, Milena; Glinkowski, Wojciech; Marciniak, Katarzyna; Klajn, Natalia; Kesy, Jacek; Kopcewicz, Jan (Frontiers in Plant Science, 2017)
Yellow lupine (Lupinus luteus L., Taper c.), a member of the legume family (Fabaceae L.), has an enormous practical importance. Its excessive flower and pod abscission represents an economic drawback, as proper flower and seed formation and development is crucial for the plant's productivity. Generative organ detachment takes place at the basis of the pedicels, within a specialized group of cells collectively known as the abscission zone (AZ). During plant growth these cells become competent to respond to specific signals that trigger separation and lead to the abolition of cell wall adhesion. Little is known about the molecular network controlling the yellow lupine organ abscission. The aim of our study was to establish the divergences and similarities in transcriptional networks in the pods, flowers and flower pedicels abscised or maintained on the plant, and to identify genes playing key roles in generative organ abscission in yellow lupine. Based on de novo transcriptome assembly, we identified 166,473 unigenes representing 219,514 assembled unique transcripts from flowers, flower pedicels and pods undergoing abscission and from control organs. Comparison of the cDNA libraries from dropped and control organs helped in identifying 1,343, 2,933 and 1,491 differentially expressed genes (DEGs) in the flowers, flower pedicels and pods, respectively. In DEG analyses, we focused on genes involved in phytohormonal regulation, cell wall functioning and metabolic pathways. Our results indicate that auxin, ethylene and gibberellins are some of the main factors engaged in generative organ abscission. Identified 28 DEGs common for all library comparisons are involved in cell wall functioning, protein metabolism, water homeostasis and stress response. Interestingly, among the common DEGs we also found an miR169 precursor, which is the first evidence of micro RNA engaged in abscission. A KEGG pathway enrichment analysis revealed that the identified DEGs were predominantly involved in carbohydrate and amino acid metabolism, but some other pathways were also targeted. This study represents the first comprehensive transcriptome-based characterization of organ abscission in L. luteus and provides a valuable data source not only for understanding the abscission signaling pathway in yellow lupine, but also for further research aimed at improving crop yields.